Holistic approach to quantum cryptography in cyber security - Shashi Bhushan, 1928- (Boca Raton : CRC Press, 2022)
"This new book discusses the concepts while also highlighting the challenges in the field of quantum cryptography, also covering cryptographic techniques and cyber security techniques, in a single volume. It comprehensively covers important topics in the field of quantum cryptography with applications, including quantum key distribution, position-based quantum cryptography, quantum teleportation, quantum e-commerce, quantum cloning, cyber security techniques architectures and design, cyber security techniques management, software defined networks, and cyber security techniques for 5G communication. The text also discusses the security of practical quantum key distribution systems, applications and algorithms developed for quantum cryptography, as well as cyber security through quantum computing and quantum cryptography. The text will be beneficial for graduate students, academic researchers, and professionals working in the fields of electrical engineering, electronics and communications engineering, computer science, and information technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Data encryption (Computer science); Computer networks -- Security measures; Quantum cryptography; COMPUTERS / Computer Engineering; TECHNOLOGY / Electronics / General